Perceptions of Clostridium difficile infections among infection control professionals in Taiwan - Yuan-Pin Hung; Jen-Chieh Lee; Hsiao-Ju Lin; Chun-Wei Chiu; Jia-Ling Wu; Hsiao-Chieh Liu; I-Hsiu Huang; Pei-Jane Tsai; Wen-Chien Ko (Journal of Microbiology, Immunology and Infection, 2017)
Background: High Clostridium difficile colonization and infection rates among hospitalized patients had been noted in Taiwan. Nevertheless, the cognition about clinical diagnosis and management of CDI among infection control professionals in Taiwan is not clear. Material and methods: A 24-item survey questionnaire about the diagnosis, therapy, or infection control policies toward CDI was distributed in the annual meeting of the Infectious Disease Society of Taiwan (IDST) in October 2015 and Infectious Control Society of Taiwan (ICST) in April 2016. Results: Totally 441 individuals responded to the survey, and 280 (63.5%) participants would routinely monitor the prevalence of CDI and 347 (78.7%) reported the formulation of infection control policies of CDI in their hospital, including contact precaution (75.7%), wearing gloves (88.9%) or dressing (80.0%) at patient care, single room isolation (49.7%), preference of soap or disinfectant-based sanitizer (83.2%) and avoidance of alcohol-based sanitizer (63.3%), and environmental disinfection with 1000 ppm bleach (87.1%). For the timing of contact precaution discontinuation isolation for CDI patients, most (39.9%) participants suggested the time point of the absence of C. difficile toxin in feces. To treat mild CDI, most (61.9%) participants preferred oral metronidazole, and for severe CDI 26.1% would prescribe oral vancomycin as the drug of choice. Conclusion: There were substantial gaps in infection control polices and therapeutic choices for CDI between international guidelines and the perceptions of medical professionals in Taiwan. Professional education program and the setup of guideline for CDI should be considered in Taiwan.